2010
DOI: 10.1001/archinternmed.2010.197
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Individual Antiretroviral Drugs on the Risk of Myocardial Infarction in Human Immunodeficiency Virus–Infected Patients<subtitle>A Case-Control Study Nested Within the French Hospital Database on HIV ANRS Cohort CO4</subtitle><alt-title>Antiretroviral Drugs, Risk of MI, and HIV</alt-title>

Abstract: The risk of MI was increased by cumulative exposure to all the studied PIs except saquinavir and particularly to amprenavir/fosamprenavir with or without ritonavir and lopinavir with ritonavir, whereas the association with abacavir cannot be considered causal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
224
4
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 271 publications
(238 citation statements)
references
References 25 publications
6
224
4
4
Order By: Relevance
“…In the French cohort [18], the recent use of fosamprenavir was associated with a higher incidence of acute myocardial infarction. There is increasing concern about cardiovascular morbidity and mortality in patients with HIV infection, and about this fact specific guides to risk management have been published and various studies were conducted to elucidate the role that some component of HAART may have in ischaemic events.…”
Section: Discussionmentioning
confidence: 97%
“…In the French cohort [18], the recent use of fosamprenavir was associated with a higher incidence of acute myocardial infarction. There is increasing concern about cardiovascular morbidity and mortality in patients with HIV infection, and about this fact specific guides to risk management have been published and various studies were conducted to elucidate the role that some component of HAART may have in ischaemic events.…”
Section: Discussionmentioning
confidence: 97%
“…Current receipt of highly active antiretroviral therapy (HAART) was defined as the use of three or more antiretroviral drugs as per the guidelines [33]. Specific NRTIs (abacavir, tenofovir and didanosine) and PIs (ritonavir, atazanavir) were examined based upon the number of users as well as published studies showing that some antiretroviral medications may be associated with increased CAD risk [11][12][13].…”
Section: Clinical Data Collectionmentioning
confidence: 99%
“…Additionally, some studies suggest that HIV patients are experiencing accelerated vascular aging [5,6], although further data are needed. The exact risk factors for the higher risk of cardiovascular disease among HIV patients are unclear, but likely related to complex interactions between the virus itself, antiretroviral medications, increased immune activation, and metabolic changes [3,4,[7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Another large-scale study that included more than 23,000 HIV patients analyzed the combination of drugs used in HAART and concluded that protease inhibitors (PIs) are associated with an increased risk of cardiovascular disease, which is partly explained by dyslipidemia (Friis-Moller et al, 2007). A Swiss HIV Cohort Study found that PIs are the cause of dyslipidemia in patients (Periard et al, 1999), and several other studies have reached the same conclusion (Stein et al, 2001;Lang et al, 2010). Despite the strong evidence linking PIs with dyslipidemia and cardiovascular disease, the underlying mechanisms responsible for the adverse effects of PIs remain elusive.…”
Section: Introductionmentioning
confidence: 99%
“…However, HAART has also been associated with dyslipidemia and an increased risk of cardiovascular disease (Carr et al, 1998;Periard et al, 1999;Distler et al, 2001;Stein et al, 2001;Friis-Moller et al, 2003Lang et al, 2010). For example, findings from the Data Collection on Adverse Events of Anti-HIV Drugs (DAD) study suggested that the incidence of cardiovascular disease increased with longer exposure to HAART (Friis-Moller et al, 2003).…”
Section: Introductionmentioning
confidence: 99%